2018
DOI: 10.1016/j.pocean.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Wave modelling in coastal and inner seas

Abstract: In the long term development of the research on wind waves and their modelling, the present situation is framed with a short look at the past, a critical analysis of the present capabilities and a foresight of where the field is likely to go. After a short introduction, Chapter 2 deals with the basic processes at work and their modelling aspects. Chapter 3 highlights the interaction with wind and currents. Chapter 4 stresses the need for a more complete, spectral, approach in data assimilation. Chapter 5 summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
107
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(109 citation statements)
references
References 386 publications
(386 reference statements)
1
107
0
1
Order By: Relevance
“…For example, Clementi et al (2017) introduced a relatively reduced-complexity coupling of the mean momentum transfer of waves and wind speed stability parameter between the WAVEWATCH III wave model (Tolman et al, 2004) and NEMO ocean model codes. They demonstrated that for the Mediterranean Sea while the coupling was found to improve wave performance, there was limited impact on mean SST results over the 5-year study period.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Clementi et al (2017) introduced a relatively reduced-complexity coupling of the mean momentum transfer of waves and wind speed stability parameter between the WAVEWATCH III wave model (Tolman et al, 2004) and NEMO ocean model codes. They demonstrated that for the Mediterranean Sea while the coupling was found to improve wave performance, there was limited impact on mean SST results over the 5-year study period.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these improvements, the quality of the wave forecasts is still not sufficient in the coastal and semienclosed seas (Cavaleri et al 2018). Their performance has not been extensively evaluated in complex coastal areas and / Published online: 3 December 2019 their results cannot be used with as high level of reliability as for the open sea.…”
Section: Introductionmentioning
confidence: 99%
“…Models such as ECMWF, AdCirc, Wavewatch III help provide a detailed description of the wind, currents and wave climate [32], both in terms of extremes and average values. In some cases, it is useful to statistically analyse the forcing provided by extensive databases (e.g., NOAA's Historical Hurricane Tracks [33]).…”
Section: Data Integration By Numerical Modellingmentioning
confidence: 99%